The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.ejcts.2006.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Absent pulmonary valve syndrome.☆Surgical and clinical outcome with long-term follow-up

Abstract: The surgical outcome of APVS was closely related to preoperative ventilator dependency. Efforts to improve the surgical outcome should be focused on identifying and correcting this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…Norgaard et al inserted monocusp pulmonary valves from a variety of materials in 39% of the total corrective surgeries performed on 36 patients with APVS and TOF. They found no significant survival differences between the groups having no pulmonary valve, monocusp valves, and homograft conduits …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Norgaard et al inserted monocusp pulmonary valves from a variety of materials in 39% of the total corrective surgeries performed on 36 patients with APVS and TOF. They found no significant survival differences between the groups having no pulmonary valve, monocusp valves, and homograft conduits …”
Section: Discussionmentioning
confidence: 94%
“…They found no significant survival differences between the groups having no pulmonary valve, monocusp valves, and homograft conduits. 25 Total corrective surgery, including reconstruction of the pulmonary valve with a homograft or a heterograft, may be appropriate by the end of infancy. McCaughan et al 8 reported clinical improvement and symptom reduction in patients with APVS and TOF with a single pulmonary artery after the creation of a conduit via surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect of the natural history of APVS emphasises the importance of early diagnosis and intervention before the onset of severe cardiorespiratory distress. The impact of respiratory distress at the time of surgical intervention can also be seen in a large case series by Norgaard et al ,5 where preoperative ventilator dependency was the strongest negative predictor of postoperative survival.…”
Section: Discussionmentioning
confidence: 78%
“…If children with absent pulmonary valve have early surgery with correction of the cardiac defects and pulmonary angioplasty or translocation, the prognosis is good [17, 23]. …”
Section: Discussionmentioning
confidence: 99%